Academic Performance and Perception of Learners in Technology Subjects: A Flexible Learning Assessment - Segumpan, Shiela Mae Icalina; Segumpan@gmail.com, Lester Lou Benguar (FKIP Universitas Lampung, 2023)
Academic Performance and Perception of Learners in Technology Subjects: A Flexible Learning Assessment. This study compared the academic performance of the learners in flexible learning (FL) and face-to-face and determined the correlation of student perceptions and academic performance of the students in Technology subjects. The longitudinal and descriptive correlation research design were employed. Descriptive statistics was used to assess the learners' academic performance and ascertain their perception in FL. The paired-sample t-test was utilized to determine if there's a significant difference in the learners' academic performance. The Pearson Coefficient Binomial Correlation was used to determine if there's a significant relationship between their perception and academic performance. The results showed that their academic performance is very high, both FL and face-to-face. Also, the results revealed no significant difference in the learners' academic performance. Finally, the learners' perception is moderate, showing no significant relationship between the learners' perception and academic performance in FL. Keywords: flexible learning, academic performance, perception.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202346